The Effect of Company Operational Complexity, Profitability, Solvency, Audit Tenure, and Financial Distress on Audit Delay During the Pandemic - Fajar Apriyustiono; Muhammad Abdul Aris (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates the impact of factors like operational complexity, profitability, solvency, audit tenure, and financial distress on audit delays among mining companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. Secondary data is obtained from the companies' annual financial reports, with data analysis conducted through descriptive statistics and multiple linear regression methods. The findings reveal that while company operations complexity and profitability negatively influence audit delays, the other variables do not show a significant effect. These findings are expected to provide insights for company management and auditors regarding factors influencing audit delay, especially in the pandemic context.